RESPONSE OF DATE OF SOWING ON YIELD AND YIELD ATTRIBUTES OF SAFFLOWER CULTIVARS - SAHU, JYOTIMALA; THAKUR, N. S. (The Bioscan, 2016)
In order to investigate the “Response of Date of Sowing on Yield and Yield Attributes of Safflower Cultivars” an experiment was conducted on a split plot design with 4 replications during the year 2013-14 at Indore (M.P.). The experiment consisted of 9 treatment combinations comprising 3 dates of sowing (1st November, 15th November, 30th November) as main plots and 3 cultivars (A-1, NARI-6, NARI-57 ) as subplots. The result showed that sowing of safflower on 1st November recorded significantly higher Yield and Yield attributing characters viz.; number of capitula/plant (26.21), weight of capitula (78.60 g plant-1), number of seeds capitula-1 (22.21), 100 seed weight (6.20 g), higher seed yield (1701 kg ha-1), straw yield (5683 kg ha-1) and biological yield (7384 kg ha-1) as compared to 15th November and 30th November respectively. Among the cultivars of safflower, A-1 had significantly higher yield and yield attributing characters viz., capitula/plant (27.21), weight of capitula (96.72 g plant-1), and 100 seed weight (6.55 g), higher seed yield (1700 kg ha-1), straw yield (5535 kg ha-1) and biological yield (7235 kg ha-1) over NARI-57 and NARI-6. From the study it can be concluded that combination of cultivar A-1 sown in 1st November performed best among all other treatment combinations.